Density Identification of Rats and Fleas (Xenopsylla Cheopis) as the Biological Vector of Plague at the Central Market of Gorontalo City - Tri Septian Maksum; Sarinah Basri K.; Putri Ayuningtias Mahdang (Universitas Muhammadiyah Palu, 2023)
Rat are a reservoir for bubonic plague, as well as a host for ectoparasites of the flea type (Xenopsylla cheopis) as the main biological vector that contributes to the transmission of bubonic plague. Traditional markets are one of the places where rats can be found in quite high numbers. This study aims to determine the density of rats and the presence of fleas (Xenopsylla cheopis) in rats at the Gorontalo City Central Market. The type of research used in this research is descriptive quantitative. The samples were rats caught using mouse traps which were spread at 10 points for 3 days and fleas (Xenopsylla cheopis) that lived on rats. The data is presented using tables and then analyzed descriptively The results showed that the density of rats at the Gorontalo City Central Market was 60%, meaning that it was classified as high density (exceeding the Environmental Health Quality Standards according to Permenkes No. 50 of 2017, namely > 5%). The density of fleas (Xenopsylla cheopis) at the Gorontalo City Central Market is 0.116, meaning that it does not have the potential to transmit bubonic plague (under the Environmental Health Quality Standard according to Permenkes No.50 of 2017, namely <1). It is suggested to market managers be able to control the rat vector using physical control in the form of setting traps and chemical control in the form of administering rat poison, as well as improving the environment around the market to reduce the rat population.